Performance Assessment of Interaction Soil Pile Structure Using the Fragility Methodology - Guettafi Nesrine; Yahiaoui Djarir; Abbeche Khelifa; Bouzid Tayeb (Salehan Institute of Higher Education, 2021)
This study aimed to investigate whether the seismic fragility and performance of interaction soil-pile-structure (ISPS) were affected by different parameters: axial load, a section of the pile, and the longitudinal steel ratio of the pile were implanted in different type of sand (loose, medium, dense). In order to better understand the ISPS phenomena, a series of nonlinear static analysis have been conducted for two different cases, namely: (i) fixed system and (ii) ISPS system, to get the curves of the capacity of every parameter for developing the fragility curve. After a comparison of the numerical results of pushover analysis and fragility curves, the results indicate that these parameters are significantly influenced on lateral capacity, ductility and seismic fragility on the ISPS. The increasing in the axial load exhibit high probabilities of exceeding the damage state. The increase in pile section and longitudinal steel ratio, the effect of probability damage (low and high) are not only related to the propriety geometrically, but also related to the values of ductility and lateral capacity of the system. Doi: 10.28991/cej-2021-03091660 Full Text: PDF